2019
DOI: 10.1016/j.pec.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

When chemotherapy fails: Emotionally charged experiences faced by family caregivers of patients with advanced cancer

Abstract: Objective: To explore family caregivers' emotional experiences while caring for patients with advanced cancer and navigating distressing information, awareness of dying, and difficult decisions.Methods: Qualitative descriptive study of semi-structured interviews with 92 bereaved caregivers of patients with advanced cancer. Interviews explored caregivers' experiences as patients transitioned out of active cancer treatment and neared the end of life.Results: Included in caregivers' characterization of this trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 56 publications
1
55
0
Order By: Relevance
“…Caregivers may find it challenging to convince their loved ones of a poor prognosis or may even collude with the patient's optimism, inducing distress. This association has been shown in a prior study 17 . Caregivers may also have the added pressure of planning for end‐of‐life care in the midst of patient's optimism.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Caregivers may find it challenging to convince their loved ones of a poor prognosis or may even collude with the patient's optimism, inducing distress. This association has been shown in a prior study 17 . Caregivers may also have the added pressure of planning for end‐of‐life care in the midst of patient's optimism.…”
Section: Discussionsupporting
confidence: 68%
“…Studies have shown that disagreements between patients and caregivers in the reporting of symptoms, the description of treatment side effects and benefits, and estimates of prognosis are common 7,14‐16 . Disagreement between patients and caregivers about treatment benefits, care decisions, and the patient's health is associated with negative outcomes, such as increased patient depression 14 as well increased caregiver anxiety, distress, depression, and burden (ie, the latter refers to stress experienced by caregivers from providing care for patients) 16‐19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time during which the caregiver provides care and the severity of the symptoms may impact the degree of depression they may suffer [10,11]. However, some studies indicate that it may not be the disease's duration overall, but more specifically, the terminal phase duration, associated with a significant emotional impact on family caregivers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Social research on prognosis has revealed some of the interpersonal aspects of clinical encounters including the use of evasion, euphemism and anecdotes of outliers in order to maintain hope, preserve patient–clinician relationships and foreground a ‘silver lining’ within bad news 22–24. Of the research that has been completed on caregivers’ experiences of prognosis in oncology environments, the majority has been conducted in palliative care settings,25 26 with a focus on concerns specific to the end of life, and the negative impacts on caregivers’ quality of life 27. We still have very little knowledge about how caregivers experience prognostic encounters around cancer, including how they navigate their own need for knowledge and understanding (eg, certainty and realism), alongside the needs of the person for whom they are caring (eg, hope and optimism).…”
Section: Introductionmentioning
confidence: 99%